An Exploratory Analysis of the Role of Adipose Characteristics in Fulltime Wheelchair Users’ Pressure Injury History - Sonenblum, Sharon Eve; Measel, Megan; Sprigle, Stephen H.; Greenhalgh, John; Cathcart, John McKay (Frontiers in Bioengineering and Biotechnology, 2021)
Aim: The goals of this study were 1) to identify the relationship between adipose (subcutaneous and intramuscular) characteristics and pressure injury (PrI) history in wheelchair users, and 2) to identify subject characteristics, including Biomechanical Risk, that are related to adipose characteristics. Materials and Methods: The buttocks of 43 full-time wheelchair users with and without a history of pelvic PrIs were scanned in a seated posture in a FONAR UPRIGHT® MRI. Intramuscular adipose (the relative difference in intensity between adipose and gluteus maximus) and the subcutaneous adipose characteristics (the relative difference in intensity between subcutaneous adipose under and surrounding the ischium) were compared to PrI history and subject characteristics. Results: Participants with a history of PrIs had significantly darker adipose under the ischium than surrounding the ischium than participants without a history of PrIs. On the other hand, only when individuals with complete fat infiltration (n=7) were excluded, did individuals with PrI history have more fat infiltration than those without a PrI history. Presence of spasms and fewer years using a wheelchair were associated with leaner muscle. Conclusion: Understanding the changes in SubQF characteristics associated with PrI development may help our understanding of the aetiology of PrI development and improve our ability to prevent PrIs. Additionally, based on these findings, exploring the role of intramuscular fat infiltration in PrI development will be important.